Attentional Focus Instructions Do Not Affect Choice Reaction Time - Ziv, Gal; Lidor, Ronnie (Frontiers in Psychology, 2021)
Studies on attentional focus have shown that participants who were instructed to focus externally performed better than those who were taught to focus internally. However, in most of these studies the participants performed complex motor tasks. Due to the scarcity of data on the effects of attentional focus specifically on simple motor tasks, our purpose in the current study was to examine these effects on two simple reaction time (RT) tasks. The study was conducted on a cloud-based experimental software. Participants were allocated to three experimental groups: an external focus group (n = 44), an internal focus group (n = 46), and (c) a control group (no attentional instructions) (n = 47). The participants performed two tasks: a choice-RT task and a Simon task. Participants in all three groups practiced eight blocks of 20 trials from each task in a counterbalanced order – a total of 180 trials for each task. The sole difference between the three groups was the administered attentional focus instructions. The findings suggest that attentional focus instructions do not affect the performance of a choice-RT task or a Simon-task in a computerized online study. It is possible that the simple RT-based tasks in the current study were not sensitive to the attentional focus manipulation, since in such simple tasks there are not many actions that internal focus can disrupt. Although we asked the participants to what extent they followed the instructions, we cannot say whether their responses represent their actual attentional focus when performing the tasks.